Quality of life among lower limb prosthetic users in Jordan: a cross-sectional study using the Arabic SF-36 - Alfatafta, Mahmoud; Alfatafta, Huda; Alshawabka, Amneh; Atallah, Huthaifa; McGarry, Anthony (Frontiers in Rehabilitation Sciences, 2025)
IntroductionLower limb amputation is a life-altering event that affects multiple dimensions of quality of life (QoL), including physical functioning, emotional well-being, and social participation. Despite the clinical importance of QoL assessment in prosthetic rehabilitation, few studies have examined the multidimensional impact of amputation and prosthesis use in the Jordanian context. This study aimed to evaluate the QoL of lower-limb prosthetic users in Jordan and examine potential differences based on gender, and amputation level.MethodsA cross-sectional study was conducted with 293 adults with lower limb amputations, using prostheses. Participants completed the Arabic version of the RAND 36-Item Health Survey (SF-36). Data were collected from public and private rehabilitation centers across Jordan. Eight QoL subscales were scored on a 0–100 scale. Descriptive statistics, group comparisons (gender and age group), and multiple linear regression were conducted to assess predictors of QoL.ResultsThe highest domain scores were observed in Emotional Well-being (median = 77.0, IQR 55.0–90.0) and Social Functioning (median = 100.0, IQR 62.5–100.0), while the lowest were in Role Physical (median = 50.0, IQR 0.0–100.0) and General Health (median = 41.7, IQR 33.3–58.3). Group comparisons revealed significant differences by amputation level in Role Physical, Role Emotional, and Composite QoL scores, with individuals with more proximal amputations reporting lower outcomes. Regression analyses showed that older age significantly predicted poorer Physical Functioning (β = –0.75, p < 0.001), and male participants scored higher than females in the same domain (β =  + 8.67, p = 0.0227). Amputation level was significantly associated with QoL in select domains in group comparisons, though it was not a significant predictor in multivariable regression. Education level was not a significant factor in either analysis. The models explained a modest proportion of variance, with R² values ranging from 0.03 to 0.19 across SF-36 domains.ConclusionsLower limb prosthetic users in Jordan experience moderate impairments in physical QoL domains, particularly among older adults. Emotional and social domains were relatively preserved. Demographic factors, especially age and gender were associated with differences in specific QoL outcomes and should be considered in the development of personalized rehabilitation strategies.